The Role of Internet Usage on Gender Wage Gap: Evidence From Indonesia - Dewi, Martina Nurma; Damayanti, Arie (Journal of Developing Economies, 2025)
This study analyzes the effect of internet usage on the gender wage gap within Indonesia’s labor market. Using data from the 2022 National Labor Force Survey (Sakernas), the research employs robust least square regression, quantile regression, and the Oaxaca-Blinder Decomposition Method to assess the differential effects of internet use on wages across genders. The findings indicate that internet usage in main job significantly increases wages for both men and women while also narrowing the gender wage gap which varies by income level and job type. This effect is more pronounced in white-collar jobs and among higher-income groups compared to blue-collar jobs and middle-income groups. Additionally, the study underscores that unexplained factors, including discrimination, play a significant role in perpetuating the gender wage gap.